Estonian foreig policy 1939–1940 - Ilmjärv, Magnus (Genocidas ir rezistencija, 2000)
This presentation analyses what Tallinn knew about the secret protocols to the Molotov–Ribbentrop Pact. It then presents the Estonia’s foreign policy in September 1939 and during the Winter War. The presentation concludes with an overview of foreign policy in the second half of the 1920s and a comparison of the situation in Estonia with events in Finland.